DESIGNING AND IMPLEMENTATION OF LIQUID TRANSFER MAINTENANCE STANDARD OPERATION PROCEDURE IN PT.NIGI - Ni’matul Ma’muriyah; Satria Wijaya; Dian Tresnawan (Universitas Internasional Batam, 2022)
Community service was carried out at the Widi Shop which was established in 2016. This shop sells various kinds of food and beverages, as well as various other household needs. Writing this report is intended to assist shop owners in making bookkeeping and inventory effectively and safely. Information collection techniques are based on primary information sources, where research information is obtained directly from first-person sources, while for data collection techniques, the practitioner conducts interviews and observations during the community service. Based on the evaluation of community service, it was concluded that digital bookkeeping was more effective, resulting in increased store revenue 12,1% compared to the previous month and the data are more secure than the traditional bookkeeping and the impact of implementing the activities are that Toko Widi is aware of the importance of digital bookkeeping and stock availability which mean the community service is 100% success.